2016
DOI: 10.21894/jopr.2016.2802.07
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Succession in Co-Composting of Chipped-Ground Oil Palm Frond and Palm Oil Mill Effluent

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
2
2
Order By: Relevance
“…This phenomenon was caused by the small size of EFB that were easily digested by the microbes. In the thermophilic phase of this study, the population of microbe colony was lower than that found in Ahmad et al's study [23] which obtained a microbial population of around 66 x 10 10 cfu/g, and then subsided to 9.0 x 10 10 cfu/g on 60 days of the composting. The decrease in composting temperature was followed by a decrease in the number of bacteria.…”
Section: Bacteria Concentrationcontrasting
confidence: 77%
See 2 more Smart Citations
“…This phenomenon was caused by the small size of EFB that were easily digested by the microbes. In the thermophilic phase of this study, the population of microbe colony was lower than that found in Ahmad et al's study [23] which obtained a microbial population of around 66 x 10 10 cfu/g, and then subsided to 9.0 x 10 10 cfu/g on 60 days of the composting. The decrease in composting temperature was followed by a decrease in the number of bacteria.…”
Section: Bacteria Concentrationcontrasting
confidence: 77%
“…These values indicated that biosludge of pulp and paper had high organic matter. In comparison, the COD value in this study was lower than the anaerobic palm oil mill effluent that was obtained by Ahmad et al [23] where the COD valued 40,563 mg/l [23]. Meantime, the BOD value in this study was higher than in Baharuddin et al [10] which had a range between 1,000-2,600 mg/l.…”
Section: Raw Materials Characterizationcontrasting
confidence: 68%
See 1 more Smart Citation
“…The composition of the Chromatiaceae in the system introduced with POME final discharge increased starting from day 2 (2.2%) to day 7 (5.1%), then reduced after the implementation of zero-emission of POME final discharge on day 8 (2.2%) and became undetectable on day 15. This can be explained by the association of Chromatiaceae composition with the degradation of dissolved organic carbon (DOC) present in the POME [58]. On the other hand, the composition of Alcaligenaceae showed a small reduction from 1.2% on day 8 to 0.9% on day 15.…”
Section: Classmentioning
confidence: 99%